Tindak Pidana Pembobolan Dana Nasabah dapat Mengurangi Kepercayaan Masyarakat terhadap Industri Perbankan - Muhammad Zen Abdullah (Legalitas: Jurnal Hukum, 2020)
The development of the banking industry by entering the current era of globalization and liberalization of financial markets, has resulted in increased competition among banks, especially in fund raising. Therefore, bank management is required to have the skills to manage the bank's wealth, debt and capital reflected in the bank's balance sheet well. A more fundamental of the expertise and skills in managing the bank, it is necessary to be careful and followed by the good faith of the bank management, ranging from the board of commissioners, directors and employees of the bank. This means that bank managers should be the party that always adheres to the high code of banking ethics and complies with all applicable laws and regulations in the banking sector. But in practice, it is not always possible to run well if it is not covered by the possibility of food-storage that leads to fraud by breaking customer funds conducted internally by the bank itself. Of these problems raises fundamental questions, namely (1) What causes the criminal breach of customer funds in the banking industry, and (2) How to resolve the criminal breach of customer funds in the banking industry. To answer both questions, legal research methods are used. Normative juridical approach (legal research), namely research on positive laws by evaluating the relevant rule of law. This approach identifies and codified the law as the norm, rules, regulations related to the criminal breach of customer funds in the banking industry.